A flow‐through microfluidic chip for continuous dielectrophoretic separation of viable and non‐viable human T‐cells. Issue 3 (30th November 2021) - Mustafa, Adil; Pedone, Elisa; Marucci, Lucia; Moschou, Despina; Lorenzo, Mirella Di
Abstract: Effective methods for rapid sorting of cells according to their viability are critical in T cells based therapies to prevent any risk to patients. In this context, we present a novel microfluidic device that continuously separates viable and non‐viable T‐cells according to their dielectric properties. A dielectrophoresis (DEP) force is generated by an array of castellated microelectrodes embedded into a microfluidic channel with a single inlet and two outlets; cells subjected to positive DEP forces are drawn toward the electrodes array and leave from the top outlet, those subjected to negative DEP forces are repelled away from the electrodes and leave from the bottom outlet. Computational fluid dynamics is used to predict the device separation efficacy, according to the applied alternative current (AC) frequency, at which the cells move from/to a negative/positive DEP region and the ionic strength of the suspension medium. The model is used to support the design of the operational conditions, confirming a separation efficiency, in terms of purity, of 96% under an applied AC frequency of 1.5 × 10 6 Hz and a flow rate of 20 μl/h. This work represents the first example of effective continuous sorting of viable and non‐viable human T‐cells in a single‐inlet microfluidic chip, paving the way for lab‐on‐a‐chip applications at the point of need.